Molecular and Physiological Comparison of Spoilage Wine Yeasts - Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V (2013)
Aims: Dekkera bruxellensis and Pichia guilliermondii are contaminating yeasts in wine due to the production of phenolic aromas. Although the degradation pathway of cinnamic acids, precursors of these phenolic compounds has been described in D. bruxellensis, no such pathway has been described in P. guilliermondii. Methods and Results: A molecular and physiological characterization of 14 D. bruxellensis and 15 P. guilliermondii phenol-producing strains was carried out. Both p-coumarate decarboxylase (CD) and vinyl reductase (VR) activities, responsible for the production of volatile phenols, were quantified and the production of 4-vinylphenol and 4-ethylphenol were measured. All D. bruxellensis and some P. guilliermondii strains showed the two enzymatic activities, whilst 11 of the 15 strains of this latter species showed only CD activity and did not produce 4-EP in the assay conditions. Furthermore, PCR products obtained with degenerated primers showed a low homology with the sequence of the gene for a phenyl acrylic acid decarboxylase activity described in Saccharomyces cerevisiae. Conclusions: D. bruxellensis and P. guilliermondii may share a similar metabolic pathway for the degradation of cinnamic acids. Significance and Impact of the Study: This is the first work that analyses the CD and VR activities in P. guilliermondii, and the results suggest that within this species, there are differences in the metabolization of cinnamic acids. © 2013 The Society for Applied Microbiology.